Acute exercise reverses aged-induced impairments in insulin signaling in rodent skeletal muscle - Pauli, Jose R.; Ropelle, Eduardo R.; Cintra, Dennys Esper; De Souza, Claudio Teodoro; da Silva, Adelino S. R.; Moraes, Juliana C.; Prada, Patricia O.; de Almeida Leme, Jose A. C. [UNESP]; Luciano, Eliete [UNESP]; Velloso, Licio A.; Carvalheira, Jose B. C.; Saad, Mario J. A. (Elsevier B.V., 2010)
The insulin resistance associated with aging is improved by exercise, but the molecular mechanisms of this improvement are not fully understood. We investigated whether the improvement in insulin action, associated with acute exercise in old rats is dependent on the modulation of pIRS-1Ser307, JNK, IkB alpha and PIP-1B. Aging rats were subjected to swimming for two 1.5-h long bouts, separated by a 45 min rest period. Sixteen hours after the exercise, the rats were killed and proteins from the insulin signaling pathway were analyzed by immunoblotting. Our results show that the reduction in glucose disappearance rate (Kitt), observed in aged rats, was restored at 16 h after exercise. Aging led to an increase in Ser307 phosphorylation of IRS-1, and this was reversed by exercise in the skeletal muscle, in parallel with a reduction in pJNK and IkB alpha degradation. Moreover, aging induced an increase in the expression of PTP-1B and attenuated insulin signaling in the muscle of rats, a phenomenon that was reversed by exercise. Interestingly, the decrease in PTP-1B expression in the muscle of exercised old rats was accompanied by an increase in SIRT1 expression. These results provide new insights into the mechanisms by which exercise restores insulin sensitivity during aging. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Aging; Acute exercise; Insulin signaling and inflammation